Implementation of Islamic character education in developing religious moderation at vocational high school - Hilmi, Fuad; Annibras, Nablur Rahman; Ghani, Abdul (Atthulab: Islamic Religion Teaching and Learning Journal, 2023)
The aim of the research is the implementation of Islamic Character Education in fostering religious moderation at the Syahida Vocational High School (SMK). This study used descriptive qualitative method. Research subjects were selected using purposive sampling. Data collection techniques include: observation, interviews, and documentation. The research subjects were school principals, student affairs, Islamic religious education teachers, and students. Data analysis techniques use data collection, data reduction, data presentation, and verification. The research results show that the implementation of Islamic Character Education at Syahida Vocational School can be seen from students praying before and after studying, celebrating religious holidays, facilitating the use of worship, and tolerance in the school environment. This is proven by data verification using a data assessment rubric, that the results of observations, interviews and documentation show that the application of Islamic Character Education can produce students who are moderate in religion. The conclusion of this research is that the application of Islamic Character Education is very appropriate for forming students who are moderate in religion.Â Tujuan dari penelitian Implementasi Pendidikan Karakter islami dalam pembinaan moderasi beragama di Sekolah Menengah Kejuruan (SMK) Syahida. Penelitian ini menggunakan metode kualitatif deskriptif. Subjek penelitian dipilih secara purposive sampling. Teknik pengumpulan data meliputi: observasi, wawancara, dan dokumentasi. Subjek penelitian adalah kepala Sekolah, bidang kesiswaan, Guru Pendidikan Agama Islam, dan Siswa. Tekhnik analisis data menggunakan data collection, data reduction, data display, dan verifying. Hasil penelitian ini menunjukan bahwa implementasi pendidikan Karakter islami yang dilaksanakan di SMK Syahida dilihat siswa yang berdoa sebelum dan sesudah melakukan belajar, merayakan hari-hari besar keagamaan, memfasilitasi yang digunakan untuk beribadah, dan toleransi di lingkungan sekolah. Hal ini dibuktikan dengan verifikasi data dengan rubrik penilaian data, bahwa dari hasil observasi, wawancara, serta dokumentasi menunjukkan bahwa implementasi pendidikan karakter islami dapat menciptakan siswa yang moderat dalam beragama. Simpulan dari Penelitian ini bahwa mengimplementasikan pendidikan karakter islami sangat tepat untuk membentuk siswa yang moderat yang moderat adalam beragama.